2020
DOI: 10.1186/s12909-020-02190-6
|View full text |Cite
|
Sign up to set email alerts
|

Simulation via instant messaging-Birmingham advance (SIMBA) model helped improve clinicians’ confidence to manage cases in diabetes and endocrinology

Abstract: Background: Simulation-based learning (SBL) has been increasingly used in both undergraduate and postgraduate medical training curricula. The aim of Simulation via Instant Messaging-Birmingham Advance (SIMBA) is to create a simple virtual learning environment to improve trainees' self-reported confidence in diabetes and Endocrinology. Methods: This study was done as part of the continuous professional development for Health Education England West Midlands speciality trainees in diabetes and Endocrinology. Stan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 30 publications
0
24
0
Order By: Relevance
“…SIMBA has proven to be efficient to improve clinicians' confidence in managing various cases in diabetes and endocrinology. 7 The steps building up to a SIMBA session can be divided into two main phases (Fig 1). In the preparation phase, anonymised transcripts based on real-life cases are prepared.…”
Section: What Is Simulation Via Instant Messaging -Birmingham Advance?mentioning
confidence: 99%
“…SIMBA has proven to be efficient to improve clinicians' confidence in managing various cases in diabetes and endocrinology. 7 The steps building up to a SIMBA session can be divided into two main phases (Fig 1). In the preparation phase, anonymised transcripts based on real-life cases are prepared.…”
Section: What Is Simulation Via Instant Messaging -Birmingham Advance?mentioning
confidence: 99%
“…We have previously showed that SIMBA is effective in improving clinician confidence in managing various endocrine conditions evaluated using Kirkpatrick's model of training evaluation. 3…”
Section: Simulation Via Instant Messaging-birmingham Advance (Simba)mentioning
confidence: 99%
“…8 Facilitating SIMBA simulation via WhatsApp greatly enhances interaction and engagement in comparison to traditional forms of teaching. 3 The ubiquity of WhatsApp has made SIMBA widely accessible, with international interest and participation. 3 Additionally, Twitter (@SIMBAsimulation) and Facebook are used to advertise SIMBA sessions and attract international health professionals to participate.…”
Section: Social Mediamentioning
confidence: 99%
“…At the end of each SIMBA session, structured feedback/debrie ng is provided by the consultant, followed by a post-SIMBA survey re ecting on the learners plans to bring changes to future practice based on the experience gained through simulation. The results from previous sessions have demonstrated that SIMBA is an effective teaching model to increase participants' con dence in managing various endocrine and diabetes simulated cases (12).…”
Section: Introductionmentioning
confidence: 99%
“…Simulation via Instant Messaging-Birmingham Advance (SIMBA) is an innovative teaching model designed to construct SBL through WhatsApp (12). With its concept, SIMBA is replicating the whole learning cycle proposed by Kolb's experiential learning theory.…”
Section: Introductionmentioning
confidence: 99%